2017
DOI: 10.1177/2050313x17695717
|View full text |Cite
|
Sign up to set email alerts
|

A cola-induced hypokalemic rhabdomyolysis with electromyographic evaluation: A case report

Abstract: Objective:To report a rare case of hypokalemic rhabdomyolysis induced by the heavy and prolonged ingestion of cola-based beverages, and its uneventful recovery after kalemia normalization.Methods:We report a 38-year-old Caucasian male presented in our emergency room with a recent and progressive weakness of the lower limbs proximal muscles.Results:A dietary history revealed a prolonged ingestion of cola-based beverages. Blood tests showed severe hypokalemia and marked increase in serum creatine phosphokinase. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 9 publications
0
1
0
1
Order By: Relevance
“…Datos similares fueron hallados en varios de los casos descritos en la literatura. (10)(11)(12)(13) La ingesta de grandes cantidades de glucosa es otro mecanismo por el cual se explica la hipopotasemia de nuestro paciente. La concentración de glucosa en las bebidas cola azucaradas es de 11 gr/dl.…”
Section: Discussionunclassified
“…Datos similares fueron hallados en varios de los casos descritos en la literatura. (10)(11)(12)(13) La ingesta de grandes cantidades de glucosa es otro mecanismo por el cual se explica la hipopotasemia de nuestro paciente. La concentración de glucosa en las bebidas cola azucaradas es de 11 gr/dl.…”
Section: Discussionunclassified
“…Hypokalemia can result from decreased potassium intake, extracellular to intracellular shift, and uncompensated gastrointestinal or renal loss of serum potassium. There are multiple reports of cola-induced severe hypokalemia complicated with myopathy, rhabdomyolysis, acute kidney injury, and atrial fibrillation following the excessive consumption of those drinks [5][6][7][8]. The proposed mechanism of cola-induced hypokalemia was discussed by Tsimihodimos et al; they indicated that, when consumed excessively, the unabsorbed fructose content of cola soft drinks can cause osmotic diarrhea and subsequent gastrointestinal loss of potassium.…”
Section: Discussionmentioning
confidence: 99%